Mesencephalic Astrocyte-Derived Neurotrophic Factor (MANF) Protects Against Neuronal Apoptosis via Activation of Akt/MDM2/p53 Signaling Pathway in a Rat Model of Intracerebral Hemorrhage - Xu, Weilin; Gao, Liansheng; Li, Tao; Zheng, Jingwei; Shao, Anwen; Zhang, Jianmin (Frontiers in Molecular Neuroscience, 2018)
Neuronal apoptosis plays key roles in secondary brain injury caused by intracerebral hemorrhage (ICH). This study first reported the role of mesencephalic astrocyte-derived neurotrophic factor (MANF) in alleviating secondary brain injury through anti-apoptosis in rat model of ICH. The recombinant human-MANF(rh-MANF) and selective Akt inhibitor MK2206 was administrated intracerebroventricularly 1h after ICH. Brain water content, behavioral assessment, BBB (blood brain barrier) leakage was evaluated 24h after the induction of ICH. Western blot analysis was used to evaluate the expression level of target proteins (MANF, mouse 3T3 cell double-minute 2 (MDM2), P53, Akt, Bcl-2, Bax, and caspase-3). Terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick end labeling (TUNEL) was applied to evaluate the neuronal cell death. Besides, whether MANF was expressed in neurons was verified with double immunofluorescence staining. The results suggested that the level of MANF, and its downstream proteins, Akt, MDM2 was upregulated and reached peak at 24h after ICH. MANF was mainly expressed in neurons. The administration of rh-MANF could significantly increase the level of p-Akt, p-MDM2, Bcl/Bax ratio, but reduce the expression of p53, caspase-3 and neuronal death, thus ameliorate the neurological functions at 24h after ICH. However, these effects of rh-MANF could be obviously reversed by MK2206. MANF could exert its neuronal anti-apoptotic effects via Akt/MDM2/P53 pathways. Therefore, MANF could be a valuable drug target in the treatment of ICH.